Analisis Pengaruh Corporate Board Size dan Financial Performance Terhadap Volatilitas Return Saham Dengan Growth Opportunity Sebagai Variabel Intervening Pada Ancaman Krisis Energi Indonesia - Viki Yuni Astuti; Ratih Kusumawardhani; Alfiatul Maulida (PT SOLUSI EDUKASI BERDIKARI, 2025)
The energy crisis in Indonesia has led to fluctuations in energy sector stock prices, creating uncertainty for investors. This study aims to analyze the effect of corporate board size and financial performance on stock return volatility, with growth opportunity as an intervening variable. The research employs a quantitative method using path analysis and secondary data from 14 energy sector companies listed on the Indonesia Stock Exchange during the 2018–2022 period. The results show that board size has no direct effect on stock return volatility but has an indirect effect through growth opportunity. Financial performance positively influences stock return volatility. Overall, growth opportunity is proven to partially mediate the relationship between board size and financial performance on stock return volatility.